Evaluasi Efektivitas Kebijakan BOSDA dalam Mendukung Operasional Pendidikan di SMP Negeri 2 Sidoarjo - Oktavia Rahmadani Wahyudi; Nur Muji Arti Hidayah; Nafiza Ardita Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The Regional School Operational Assistance (BOSDA) is a local government program that plays a crucial role in supporting school operational needs that cannot be fully met through the Regular School Operational Assistance (BOS). An evaluation of the implementation of BOSDA is necessary to determine the extent to which this policy is able to effectively support school operations. This study aims to evaluate the effectiveness of the BOSDA policy in supporting the operations of SMP Negeri 2 Sidoarjo. The study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The research informants consist of representatives from the Sidoarjo Regency Education Office and BOSDA administrators at SMP Negeri 2 Sidoarjo. The evaluation was conducted based on William N. Dunn’s five dimensions of policy evaluation: effectiveness, adequacy, responsiveness, appropriateness, and implementation constraints. The results of the study indicate that BOSDA plays a crucial role in supporting school operations, particularly in meeting infrastructure needs, honoraria for support staff, and other operational requirements that cannot be funded through the Regular BOS. The quarterly disbursement of funds is considered increasingly well-organized, although challenges remain regarding administrative reporting and adjustments to changes in technical guidelines. Monitoring and evaluation conducted by the Education Office also support accountability in the use of BOSDA funds. This study recommends strengthening a digital reporting system, increasing guidance for BOSDA administrators, and ensuring timely fund disbursement so that the effectiveness of the BOSDA policy can continue to be improved.